PTU-198 Towards objective endoscopic diagnosis of early Barrett's neoplasia using fibre-optic Raman spectroscopy. (28th May 2012) - Almond, M; Hutchings, J; Kendall, C; Stone, N; Shepherd, N; Barr, H
Abstract : Introduction: Raman spectroscopy is a powerful analytical technique that can rapidly and accurately identify biochemical changes in cells that have become neoplastic. We are aiming to translate this laboratory technique into an endoscopic tool that can identify high-grade dysplasia (HGD) and early malignant change (T1a, T1sm1) within Barrett's oesophagus. Here we aim to demonstrate that a novel fibre-optic Raman probe can correctly classify the pathology of ex vivo oesophageal tissue. Methods: A custom-built Raman probe, designed to fit through the instrument channel of a standard endoscope, was used to measure Raman spectra from ex vivo oesophageal tissue following oesophagectomy, endoscopic resection, or point biopsy from patients with Barrett's oesophagus +/- neoplasia. 1s spectra were measured using a monochromatic 830 nm laser for excitation. Multivariate analysis was used to correlate Raman spectra with histopathological diagnosis and calculate probe accuracy. Results: 348 spectra were measured from ex vivo tissue from 28 patients. Fibre-optic Raman measurements were able to discriminate between HGD/adenocarcinoma and non-dysplastic Barrett's oesophagus (BO) with a sensitivity of 91% and specificity of 96%. Conclusion: Fibre-optic Raman Spectroscopy could enable endoscopic targeting of early neoplastic lesions in the oesophagus facilitating potentially curative endoscopic resection. Preparation is underway for an in vivo pilot study. Competing interests: None declared.